Analisis Wacana Kritis terhadap Pemberitaa Pembukaan Lahan di Sikirang dalam Perspektif Ekolinguistik - Muthia Ayyuni Helmi; Salma Nursyah Billa; Rahma Andien Arezsya; Resti Andini; Lawri Aulia Hasibuan; Dea Saputri (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This study aims to analyze environmental representation in news texts through ecolinguistics and Critical Discourse Analysis. The study employed a qualitative descriptive method using reports on land clearing in Sikirang Tarabintang and protected forest fires around Lake Toba as data. The findings show that the land-clearing report tends to construct a positive image through diction, framing, and ideology that emphasize food security, legality, and economic benefits, while ecological impacts receive less attention. In contrast, the forest fire report portrays nature as a damaged entity that requires protection. In conclusion, media language is not neutral, but plays a role in shaping public perceptions of the environment, either by legitimizing environmental exploitation or by strengthening ecological awareness. Keywords: ecolinguistics, Critical Discourse Analysis, framing, ideology, environment.